Phenotypic stability and genome wide association study of late blight resistance in potato genotypes adapted to the tropical highlands - Lindqvist-Kreuze, H.; Gastelo, M.; Pérez, W.; Forbes, G.; Koeyer, D. de; Bonierbale, Merideth W. (Scientific Societies, 2014)
Potato genotypes from a breeding population adapted to tropical highlands were analyzed for the stability of late blight resistance and also for marker-phenotype association. We harmonized the historical evaluation data, consisting of observations spanning 6 years from two field sites utilizing a resistance scale constructed by comparing the area under the disease progress curve (AUDPC) values of 172 genotypes with that of susceptible control ‘Yungay’. In total, 70 potato genotypes had a coefficient of variability <0.5 and were considered stable across the environments tested. A principal component analysis demonstrated that the ensemble of experiments formed two distinct groups that reflect the stability of genotype resistance to late blight. Phytophthora infestans isolates present in the experimental fields belonged to the EC-1 clonal lineage and showed variation in virulence beyond the concept of the avirulence determined by the conventionally used R1-R11 differential set. A single-nucleotide polymorphism (SNP) marker on chromosome 9 was associated with late blight resistance and linked to instability. Genotypes with either AACC or AAAC combinations for this SNP were highly resistant only in some environments, while the genotypes with the AAAA combination had more moderate levels of resistance but were stable across environments.